Christian Religious Education, Null Curriculum, Learning Strategies, and Inclusiveness in Indonesia - Prasetiawati, Prasetiawati (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This paper sought to showcase the work of the Null curriculum in light of the rapid curriculum changes in Indonesia. Christian education has not been an exception to the curriculum changes over time. The curriculum and learning strategies for Christian religious education remain at the stage of compartmentalizing the curriculum for children, youth, adults, and the elderly. The Null curriculum becomes a counterweight to become implicit in houses, churches, and schools. It attempts to be honest about each learner's existence, culture, religion, customs, and the locality of school, church, and home. It represents something of a paradox amid the onslaught of curriculum shifts. The paradoxes become crucial by incorporating procedures such as critical analysis, art, and drama as interludes in the formal curriculum, such as the current curriculum development in Indonesia (Kurikulum Merdeka). Through a qualitative method, this research was conducted by performing literature reviews using secondary sources from various recent journals that bring together Christian religious education, null curriculum, learning strategies and the dialectics of curriculum in Indonesia. Results showed that null curriculum at home, school and church levels ought to be reconsidered by curriculum users and beneficiaries as part of null curriculum participation in content, flow of change and inclusiveness. The null curriculum is an ongoing curriculum through curriculum transformation in the midst of ignoring the urgency of the dimensions of Christian orthodoxy as finalities that get responses and criticisms when encountering learning strategies in learning spaces.